A cladistic insight into the higher level classification of Baetidae (Insecta: Ephemeroptera). (18th August 2020) - Cruz, Paulo Vilela; Nieto, Carolina; Gattolliat, Jean‐Luc; Salles, Frederico Falcão; Hamada, Neusa
Abstract: Baetidae was one of the first families established for mayflies (Ephemeroptera). After more than 200 years of progressive research, Baetidae is now known as the most species‐rich family in the order. Two competing proposals of family division were proposed: Cloeoninae and Baetinae, or Protopatellata and Anteropatellata. Both classifications were established without cladistic support. The purpose of this paper is to investigate the phylogenetic relationships of the family Baetidae using morphological evidence and evaluate these classification schemes. The matrix included 245 morphological characters derived from larval and adult stages across 164 species in 98 genera. The resulting tree recovered Anteropatellata, Protopatellata and Cloeoninae as not monophyletic; Baetinae and Baetovectata were recovered as monophyletic with the same circumscription. Subimaginal and imaginal characters presented the lowest homoplastic values and were the best to understand the higher relationships. Abstract : The phylogenetic analysis of the Baetidae family, based on morphological evidence, with 99 of the 106 genera, indicates that this family is monophyletic. The resulting tree recovered Anteropatellata, Protopatellata and Cloeoninae as not monophyletic; Baetinae and Baetovectata were recovered as monophyletic with the same circumscription. Subimaginal and imaginal characters presented the lowest homoplastic values and were the best to understand the higher relationships.